Investigation of Arabic Speaking Self-Efficacy of Arabic Undergraduate Students in the Context of Various Variables - Kübra Alibaşoğlu (Yayasan Mutiara Hati Moeslem, 2026)
This reserach aims to examine the perceptions of Arabic speaking self-efficacy among undergraduate students enrolled in Arabic Translation and Interpreting, Arabic Language and Literature, and Arabic Language Teaching programs, with reference to demographic characteristics. Self-efficacy is considered a crucial factor influencing language learning success, particularly in speaking skills. This research employed a quantitative approach using a survey design. A total of 159 undergraduate students participated in the study. Data were collected using the Arabic Speaking Self-Efficacy Perception Scale and analyzed using the SPSS 15.0 statistical program. The results revealed statistically significant differences in students’ perceptions of Arabic speaking self-efficacy based on class level, type of graduated high school, and university language entrance exam scores. Students with higher academic experience and relevant educational backgrounds tended to demonstrate stronger self-efficacy. In contrast, no statistically significant differences were found based on gender, age, or academic department. These findings suggest that learning experience and educational background play a more influential role than basic demographic factors in shaping students’ Arabic speaking self-efficacy. Therefore, adaptive teaching strategies that emphasize practical language use and increased speaking opportunities are recommended to effectively enhance students’ self-efficacy in Arabic speaking skills.